Perceptions, concerns, and experiences of dental interns after accident and emergency posting: A qualitative study - K Sneha Shenoy; H N Pallavi; K Pushpanjali; Vaibhav Gupta (Journal of Indian Association of Public Health Dentistry, 2016)
Introduction: Most dentists will, at some point in their career, be faced with an in-office emergency. Dental staff must undergo training in the management of emergencies to a level based on their clinical responsibilities. Aim: To explore the perceptions, concerns, and experiences of interns after their accident and emergency posting. Materials and Methods: Focus group discussions were conducted among interns in English language in a dental college in Bangalore. Participants individually answered the facilitator's questions and measures were taken not to miss out any question with the help of probes. Both focus groups were audiotaped and lasted approximately 90 min. Audio recordings and focus group notes from the sessions were transcribed, analyzed using qualitative data analysis miner software. Results: Two focus groups were conducted by the authors among interns. After verbatim, the transcript was coded into one hundred and thirty different codes which were broadly classified under eight different categories and these categories were grouped into four different themes. Interns had good and bad experiences during their posting. They said that this experience was once in a lifetime and exposure like this will help them in future to manage emergency cases in the dental clinic. Conclusions: Dental interns were aware about their shallow knowledge of medical emergencies, and they felt there is room for improvement regarding self-estimation of competence in emergency management. Hence, they suggested that emergency postings should be introduced early in their curriculum.